(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The incidence of cancer in the oral cavity is growing rapidly every year, and the percentage of undiagnosed and advanced onco-dental diseases has already reached 60%. Before the appearance of precancerous diseases and malignant neoplasms of the oral cavity, it is caused by non-observance of a set of sanitary and hygiene measures, which is the abandonment of bad household habits, proper nutrition, oral cancer includes oral hygiene and high-quality sanitation of the oral cavity. space. The importance of this problem indicates the need to improve diagnostic and preventive methods, increase the level of "oncological vigilance" of both dentists and patients. Due to their proximity to vital organs, tumors of the face, jaws, oral cavity and neck are very dangerous diseases that cause cosmetic disorders and lead to death. They account for 13% of all other surgical dental diseases. In Russia, 78% of all cases of cancer of the oral cavity and lips are diagnosed in clinical stages III-IV, the survival rate among such patients does not exceed 5 years. It is very difficult to detect the tumor process in the early stages. The appearance and development of tumors is usually not noticed against the background of satisfactory health. Swelling is detected when the functions of the organ are disturbed. Pain occurs when the size of the tumor increases significantly, as well as when it is located near any nerve.